Remittances and the effects of FDI on economic growth and macroeconomic stability with a focus on developing countries - Rudhani, Leonora Haliti; Pira, Bujar; Hasanaj, Petrit; Rudhani, MSc. Taulant (Edelweiss Applied Science and Technology, 2025)
In the context of the ongoing economic transformation in the Western Balkans, this study explores how foreign direct investment (FDI), remittances, gross fixed capital formation, exchange rates, and inflation influence economic growth in Kosovo and Albania. Using quarterly data from 2011 to 2024 and applying ARMA regression and correlation analysis, the study sheds light on the dynamics driving growth in these two neighboring yet distinct economies. The findings reveal that while FDI and capital formation strongly stimulate growth in Kosovo, Albania’s economy appears more reliant on remittance inflows. Moreover, the analyses uncover a positive association between remittances and inflation in both countries, signaling the dual role of remittances as both growth enablers and potential inflationary pressures. The implications of the results point to the need for actions by both countries. Albania must improve its investment climate to attract diversified FDI, while Kosovo should focus on converting remittances from consumption into productive investments. Both countries stand to benefit from policy reforms that unlock the full development potential of these financial flows. By highlighting underutilized economic levers, this study offers not only empirical insights but also a timely contribution to the broader conversation on sustainable growth in emerging economies.